Breast Implant-Associated Anaplastic Large Cell Lymphoma in Australia: A Longitudinal Study of Implant and Other Related Risk Factors. (18th November 2019) - Loch-Wilkinson, Anna; Beath, Kenneth J; Magnusson, Mark R; Cooter, Rodney; Shaw, Karen; French, James; Vickery, Karen; Prince, H Miles; Deva, Anand K
Abstract: Background: Breast implant-associated anaplastic large cell lymphoma (BIA-ALCL) is an emerging cancer that has been linked to the use of textured devices. The recent increase in number and frequency of cases has led to worldwide regulatory action. Objectives: The authors aimed to longitudinally study BIA-ALCL in Australia since the index case was first reported in 2007. Methods: Confirmed historical cases were collected and then prospectively analyzed from October 2015 to May 2019. Clinical and implant exposure data were determined and compared with company sales data for 4 devices to generate implant-specific risk. Results: A total 104 cases of BIA-ALCL were diagnosed in Australia with exposure to 149 unique breast implants. The mean age of patients was 48.2 years (range, 22.4-78.5 years). They had an average time from implantation to diagnosis of 6.8 years. A total 51.7% of implants utilized in this cohort were Allergan Biocell devices. The indication for implant usage was for primary cosmetic augmentation in 70%, post-breast cancer reconstruction in 23%, and following weight loss/pregnancy in 7%. The majority of women presented with early (stage 1) disease (87.5%). The risk for developing BIA-ALCL ranged from 1 in 1947 sales (95% confidence interval = 1199-3406) for Silimed Polyurethane devices to 1 in 36, 730 (95% confidence interval = 12, 568-178, 107) for Siltex imprinted textured devices. Conclusions: Implants with higher surface area/texture seem to be more associated with BIA-ALCL in Australia. Recent regulatory action to suspend, cancel, or recall some of these higher risk devices is supported by these findings. Level of Evidence: 2: